2023
DOI: 10.1021/acs.jpcb.2c08076
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Specific Direct Translocation of the Cell-Penetrating Peptide NAF-144–67 across Bilayer Membranes

Abstract: The cell-penetrating peptide NAF-1 has recently emerged as a promising candidate for selective penetration and destruction of cancer cells. It displays numerous membraneselective behaviors including cell-specific uptake and organellespecific degradation. In this work, we explore membrane penetration and translocation of NAF-1 in model lipid bilayer vesicles as a function of lipid identity in zwitterionic phosphatidylcholine lipids mixed with anionic phosphatidylserine, phosphatidylglycerol, and phosphatidic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In previous investigations of NAF-1 44–67 and WWWK, we determined that peptide insertion past the headgroup phosphate moieties into the core of the membrane presented the primary energy barrier for permeation followed by adoption of a membrane-immersed metastable state. A more favorable membrane-immersed state resulted in more efficient peptide membrane insertion. Furthermore, we have previously observed that lipid compositions that enhanced insertion of NAF-1 44–67 into the membrane also enhanced transport of the peptide across the membrane into the vesicle interior . Thus, the solvatochromic measurements of NAF-1 44–67 insertion described herein may correlate to permeation and transport, although this may not be the case for all peptides. , …”
mentioning
confidence: 68%
See 3 more Smart Citations
“…In previous investigations of NAF-1 44–67 and WWWK, we determined that peptide insertion past the headgroup phosphate moieties into the core of the membrane presented the primary energy barrier for permeation followed by adoption of a membrane-immersed metastable state. A more favorable membrane-immersed state resulted in more efficient peptide membrane insertion. Furthermore, we have previously observed that lipid compositions that enhanced insertion of NAF-1 44–67 into the membrane also enhanced transport of the peptide across the membrane into the vesicle interior . Thus, the solvatochromic measurements of NAF-1 44–67 insertion described herein may correlate to permeation and transport, although this may not be the case for all peptides. , …”
mentioning
confidence: 68%
“…Furthermore, we have previously observed that lipid compositions that enhanced insertion of NAF-1 44−67 into the membrane also enhanced transport of the peptide across the membrane into the vesicle interior. 18 Thus, the solvatochromic measurements of NAF-1 44−67 insertion described herein may correlate to permeation and transport, although this may not be the case for all peptides. 29,30 When distributed symmetrically between bilayer leaflets, anionic lipids resulted in a higher-energy λ avg for all peptides with varying degrees of magnitude and lipid headgroup specificity (Figure 2a−c).…”
mentioning
confidence: 85%
See 2 more Smart Citations